Factor momentum das anomalias e o retorno das ações : evidências de países emergentes - Duarte, Jailson Manoel Silva (2024)
Factor Momentum is an investment strategy based on the autocorrelation of anomaly returns to form a portfolio that buys (long) factors with previous positive returns and sells (short) factors with previous negative returns. This strategy arises from the interconnection between asset prices and investor sentiment, which is influenced by uncertainty in each market. Thus, this thesis investigated the relationship between Factor Momentum, investor sentiment, and economic policy uncertainty in emerging Latin American countries (Brazil, Chile, Colombia, Mexico, and Peru). I divided the analysis into three stages: (a) analyzing the relationships between anomaly returns, investor sentiment, and economic policy uncertainty; (b) examining the influence of investor sentiment on Factor Momentum; and (c) assessing the effects of economic policy uncertainty on Factor Momentum. The results showed anomalies in Latin America, although they were less pronounced when adjusted for investor sentiment. On the other hand, uncertainty did not directly influence anomaly returns but, by moderating sentiment, reduced the number of significant anomalies. I also observed that Factor Momentum generated positive abnormal returns, particularly in strategies adjusted by individual stock momentum. Furthermore, investor sentiment amplified these returns during periods of high sentiment but did not positively impact the return of Factor Momentum from anomalies. Finally, Granger causality analysis showed that economic policy uncertainty affects investor sentiment, positively impacting the returns of Factor Momentum strategies over shorter time horizons. Therefore, investor sentiment alone does not satisfactorily explain the occurrence of Factor Momentum as initially expected. This thesis contributes to understanding the complex relationship between economic policy uncertainty, investor sentiment, and the returns of Momentum Factor strategies in Latin America emerging markets. Although surrounded by several limitations, this thesis offers a theoretical and methodological basis for future investigations and the possibility of practical applications in investment strategies based on understanding the relationship between sentiment and uncertainty in the context of financial market anomalies in these emerging countries. Investors also need to consider the role of political uncertainty in defining profitable strategies in these countries.